PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP KINERJA GURU - Masrian Fauzan; Hilman Saidi Raja Bakkol Harahap; Trisman Barus; Olivia Herpanny (Cross-border, 2019)
This study is to determine the effect both jointly and partially between transformational leadership styles and job satisfaction on teacher performance. The problem in this study is how transformational leadership style and job satisfaction affect teacher performance at Madrasah Tsanawiyan Negeri 1 Deli Serdang. This research uses quantitative methods with explanatory research using primary data and secondary data. The results of the regression analysis showed that of the three independent variables included in the regression model (transformational leadership style, job stress and job satisfaction). The transformational leadership style variable has a positive and significant effect on teacher performance at Madrasah Tsanawiyah Negeri 1 Deli Serdang. It is clear that teacher performance is influenced by the transformational leadership style (hypothesis 1 is accepted). So it can be concluded that job satisfaction has an effect on teacher performance (hypothesis 3 is accepted). The results showed that the variables transformational leadership style, job stress and job satisfaction simultaneously had a positive and significant effect on teacher performance at Madrasah Tsanawiyah Negeri 1 Deli Serdang, it can be explained that transformational leadership style, job stress and job satisfaction have an effect on teacher performance (fourth hypothesis received). The results showed that the coefficient of determination (R2) was 72.3%, and the remaining 27.7% was caused by other factors such as organizational culture, work environment, and work discipline.